2018
DOI: 10.1136/jmedgenet-2018-105330
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial PITRM1 peptidase loss-of-function in childhood cerebellar atrophy

Abstract: results in childhood-onset recessive cerebellar pathology. Severity of -related disease may be affected by the degree of impairment in cleavage of mitochondrial long peptides. Disruption and deletion of X linked regulatory segments may also contribute to severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Despite this evidence, the causal link between mitochondrial demise and neurodegeneration still remains elusive. We have recently reported that pathogenic variants in the nuclear-encoded mitochondrial peptidase PITRM1 result in childhood-onset recessive cerebellar disease leading to a slowly progressive syndrome, characterized by spinocerebellar ataxia, mild intellectual disability, psychiatric manifestations, and cognitive decline 2, 3 . The clinical picture of these patients is unusual for mitochondrial disease, with a very slow progression of cognitive and psychiatric symptoms from childhood to their late sixties 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite this evidence, the causal link between mitochondrial demise and neurodegeneration still remains elusive. We have recently reported that pathogenic variants in the nuclear-encoded mitochondrial peptidase PITRM1 result in childhood-onset recessive cerebellar disease leading to a slowly progressive syndrome, characterized by spinocerebellar ataxia, mild intellectual disability, psychiatric manifestations, and cognitive decline 2, 3 . The clinical picture of these patients is unusual for mitochondrial disease, with a very slow progression of cognitive and psychiatric symptoms from childhood to their late sixties 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, mitochondria are often considered to be a secondary target, rather than the actual disease driver in these conditions. We have recently described three independent families carrying missense loss of function mutations in pitrilysin metallopeptidase 1 (PITRM1), resulting in an age-dependent, progressive, neurological syndrome 2, 3 . Patients suffer from progressive cerebellar dysfunction leading to cerebellar atrophy, and psychiatric manifestations including obsessive behavior, anger attacks, and psychosis 2, 3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pitrm1 (encodes for PreP) knockout mice display embryonic lethality 10 . Furthermore, genetic defects in PreP are linked with human neurological disorders, e.g., cognitive disability/impairment and cerebellar atrophy 10,11 .…”
Section: Introductionmentioning
confidence: 99%